FUZZY INFERENCE SYSTEM OF TSUKAMOTO METHOD IN DECISION MAKING ON DETERMINATION OF INSURANCE PREMIUM AMOUNT FOR DUE DAMAGES OF FLOOD NATURAL DISASTER - Mohd Khairul Amri, Kamarudin; Muhammad Barzani, Gasim; Adiana, Ghazali (2018)
Floods often cause loss of buildings damage for people in the Citarum river basin. Community chooses insurance for recovery and protection against buildings damage. Insurance companies need to determine the amount of premium which is feasible and affordable by the community. This paper analyzes the fuzzy inference system (FIS) of Tsukamoto method in determining the amount of insurance premium. For the determination of the premium, the variables used include income, expenses and residence zones. The amount of premium is determined using the FIS of the Tsukamoto method. From the analysis, the average amount of premium is IDR 11,041.00 per month for community in Bojongsoang zone and IDR 11,321.00 per month for community in Baleendah zone. The amount of this premium is quite feasible and affordable by community in the two zones.